Analysis of an all-terrain tracked robot with innovative suspension system. (April 2023) - Ugenti, Angelo; Galati, Rocco; Mantriota, Giacomo; Reina, Giulio
Abstract: Tracked robots are gaining interest in the current context of off-road mobile robotics, especially in soft-terrain applications, because they offer a large contact area with the ground, which provides better traction than wheels or legs. In this paper, a novel passively articulated tracked robot is introduced. On each side, Polibot features a rubber track wrapped around four independently suspended road wheels, an idler wheel, and the sprocket, and it can adapt to many kinds of terrain. An inverse kinematic model for the proposed architecture is also developed to predict the system configuration given the terrain topography. The analytical model is based on constraint equations and a quasi-static force analysis, and it is validated against results obtained from the real prototype, showing good agreement. It can also be used to evaluate the influence of the many suspension design parameters and operating conditions, proving that it can be a useful tool for the proper setup of the robot. Highlights: New architecture of an all-terrain tracked robot. Innovative passive suspension system for high mobility over irregular terrain. Development of an inverse kinematics model for the proposed novel architecture. Validation of the analytical model with the real prototype. Analysis of the robot setup.